Aptamer-engineered nanomaterials to aid in mycotoxin determination. (May 2022) - Xiong, Ying; Li, Wang; Wen, Qian; Xu, Dong; Ren, Jiali; Lin, Qinlu
Abstract: Mycotoxin prevalence in food is a global public health issue, that could impose severe economic burdens. To prevent risk of exposure to mycotoxins, it is of great importance to develop selective, sensitive, and reliable methods to monitor mycotoxin levels in food samples. Recent advances in nanotechnology have produced many nanomaterials with unique physical features and extensive effort has been exerted to apply these nanomaterials in mycotoxin determination. Many specific aptamers, which have distinct advantages such as uniform synthesis, low cost, customizable modification, and chemical stability, have been developed to endow nanomaterials with target selective properties. Given the merits of these materials, aptamer-based nanomaterials for mycotoxin detection have received extensive attention from researchers. This review focuses on recent advances in aptamer nanomaterial-based sensing strategies used for mycotoxin analysis in food samples in the past five years. Representative examples of aptamer nanomaterial-based sensors for specific mycotoxin detection are described. The future challenges and opportunities regarding the use of aptamer-based nanomaterials to assist in the control of mycotoxins and other food contaminants are also discussed. Highlights: A systematic overview of aptamer-engineered nanomaterials to monitor mycotoxins that occur primarily in foods. Various aptamer-engineered nanomaterials for specific mycotoxin determination are reviewed. A reference for multidisciplinary collaborative innovation and research in this field.